(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
This article reports on the process of creating costumes, associated with the teaching practice, of Professor Samuel Abrantes in his Carnival studio, as well as coauthorship in their costumes, with students and carnival makers. Two case studies are listed by theauthors for the analysis of construction processes, methodology and problem solutions, over the more than 15 years in which researchers have followed their experience and work in the production of Rio carnival. In addition to the methodology and the creative process, the article describes the importance of exchanging experiences, learning horizontally within the workspace and the importance of the role of the costume designer and the trans disciplinarity that the profession requires, regardless of the media for which the costume is created. It also reinforces the importance of Praxis for the construction of a reflective theory of carnival costumes and the formation of the artist, inside and outside the academy.